85.6k views
2 votes
X² + y² - 16x + 8y = 0.
How do I convert problem into general form from standard form?

1 Answer

5 votes

Final answer:

To convert the equation x² + y² - 16x + 8y = 0 from standard form to general form, complete the square for both the x and y terms. The general form of the equation is (x - 8)² + (y + 4)² = 80.

Step-by-step explanation:

To convert the equation x² + y² - 16x + 8y = 0 from standard form to general form, you need to complete the square for both the x and y terms.

To complete the square for the x terms, you can take half of the coefficient of x (16/2 = 8) and square it (8² = 64). Similarly, for the y terms, take half of the coefficient of y (8/2 = 4) and square it (4² = 16).

Add these values to both sides of the equation to get x² - 16x + 64 + y² + 8y + 16 = 80.

Simplify the equation to (x - 8)² + (y + 4)² = 80. This is the general form of the equation.

User Kenneth Rory Dunn
by
8.3k points